Money supply endogeneity : an empirical investigation of South African data (2000Q1-2011Q4) - Schady, Stuart William (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2013)
This study is about whether the money supply in South Africa under a monetary policy regime of inflation" targeting is exogenously or endogenously determined. The proposition of an exogenous money supply has been offered by monetarists, where the Central Bank determines the quantity of money supplied to the economy and this has a causal influence on income and credit extension. The endogenous money theory is a post" Keynesian proposition whereby the money creation is determined by banks adjusting their responses to demands for credit" money from economic agents. The data analysis is from 2000Q1 to 2010Q4 and entails the use of the variables monetary base (MB), domestic credit extension (DCE), M3, and gross national product (GDP). All variables are logged. The empirical tests conducted start with the Augmented Dickey" Fuller unit root test to determine the variables order of integration. Johansen cointegration tests are done followed by Vector Error" Correction Models (VECMs) and Granger causality tests to determine whether there is unidirectional or bidirectional causality between variables over the long and short" run. Based on the results of the testing it was discovered that over the inflation" targeting regime money supply in South Africa was endogenously determined. Furthermore, the data best supports the Accommodationist analysis of endogenous money as opposed to that of Structuralism and Liquidity Preference,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Monetary policy -- South Africa; Inflation targeting -- South Africa; Gross domestic product -- South Africa; Bank loans -- South Africa; Money supply -- South Africa; Endogenous growth (Economics); Domestic credit extension